Standardization of an Experimental Murine Model of Invasive Pulmonary Aspergillosis - Sheppard, Donald C. (American Society for Microbiology, 2006)
Evaluating new therapeutic agents for invasive aspergillosis requires animal models that are reproducible among different laboratories. We therefore evaluated a murine model of aerosol infection in two independent laboratories and found a high level of both intra- and interlaboratory reproducibility of survival, fungal burden over time, and the efficacy of liposomal amphotericin B.